2015
DOI: 10.20884/1.anprod.2015.17.3.503
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacies of Banana Stem Extract as a Candidate of Coccidiostat Against Rabbit Eimeria Stiedaio Ocysts: an in Vitro Analysis

Abstract: Abstract. The objective of this research was to investigate the ability of banana stem (Musa paradisiaca) to inhibit sporulation of Eimeria stiedai oocysts derived from rabbit by in vitro analysis. Analyze the active substance proximate analysis and active substances in this research were performed too. Banana stem extract were used in this experiment and sulfaquinoxalline (Coxy®) was run as a control. The Eimeria stiedai oocysts were incubated prior the presence of different concentration from banana stem ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The other natural plant functioning as an anticoccidiosis is banana stem. Our previous in vitro test showed that banana stem extract might decrease E. stiedai oocysts (Indrasanti et al, 2015). The existing tannin contained in garlic and banana stem, as contained in pine stem extract, might significantly decrease the oocyst sporulation ability by inhibiting the enzyme activity contributing in the sporulation process, by penetrating through the oocystic cell walls and destroying the cytoplasm (sporont) that resulted in abnormal oocysts (Molan et al, 2009;Indrasanti et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other natural plant functioning as an anticoccidiosis is banana stem. Our previous in vitro test showed that banana stem extract might decrease E. stiedai oocysts (Indrasanti et al, 2015). The existing tannin contained in garlic and banana stem, as contained in pine stem extract, might significantly decrease the oocyst sporulation ability by inhibiting the enzyme activity contributing in the sporulation process, by penetrating through the oocystic cell walls and destroying the cytoplasm (sporont) that resulted in abnormal oocysts (Molan et al, 2009;Indrasanti et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The extract was further evaporated in a waterbath to produce a concentrated extract. The concentrated extract was then stored at the temperature of 5°C and ready to use (Islam et al, 2008;Iqbal et al, 2013;Indrasanti et al, 2015).…”
Section: Preparation Of Garlic Extractmentioning
confidence: 99%
“…Adding of a mixture of garlic oil and oregano to rabbit feed can also help in disease prevention (Kowalska et al, 2012;Nosal et al, 2014). Other plant extracts such as banana stem extract could decrease the number of E. stiedae oocysts in vitro (Indrasanti et al, 2015). However, Matekaire et al (2005) stated that both banana root (Musa paradisiaca) and sulphadimidine sodium treatments caused a significant decrease in oocyst excretion in rabbits.…”
Section: Alternatives To Anticoccidial Drugsmentioning
confidence: 99%